Health team for the elderly: a feasibility study for preventive home visits. Issue 3 (20th February 2017) - Seiger Cronfalk, Berit; Fjell, Astrid; Carstens, Nina; Rosseland, Lars Malvin Kvinge; Rongve, Arvid; Rönnevik, Dag-Helge; Seiger, Åke; Skaug, Knut; Ugland Vae, Karen Johanne; Hauge Wennersberg, Marianne; Boström, Anne-Marie
Abstract : The aim was to describe the development, utilization and feasibility of a model of preventive home visits, in an urban and a rural municipality in Norway. Background: Older people >65 years will rise significantly in coming years. Increased age is associated with risk of disability, illness and need for public health services. Preventive home visits is assumed to help older people to maintain their functional level longer, delaying disease and thus delaying the need for health care. Method: Descriptive explorative design describing the development, utilization and feasibility of preventive home visits in two different settings. All 77-year-old persons living at home in an urban municipality and all 75 years and older in a rural municipality were invited to participate. A questionnaire including a substantial number of tests concerning; fall, nutrition, polypharmacy and cognitive impairment was used by Health Team Nurses as base for a risk assessment. Pilot studies were conducted to validate the questionnaire including an inter-rater reliability study of the risk assessment tool. A multiprofessional team, Health Team for the Elderly met each week to evaluate risk assessments and make recommendations to be sent to each respective general practitioner. Data were analysed using descriptive and inferential statistics. In total, 167 persons (109 from the urban municipality and 58 from the rural municipality) participated, corresponding to 60% of the approached individuals. The mean time for the visits was 108 minutes (SD 20). Missing data were identified for; Do you feel safe in your municipality (17.5%) and Are you looking forward to ageing (11.4%). In total, 36 persons (21.7%) were identified with increased risk for developing illness. We suggest that a structured model of preventive home visits and collaboration between highly specialized health care professionals are important factors for reliable health promoting risk assessments of elderly home dwellers.